Differentiation Strategy and Digital Marketing for Revitalizing Traditional Retail Stores - Fauzan Daffa; Mochammad Mukti Ali; Nunung Ayu Sofiati; Ade Salman Alfarisi; Irving Irving Ignatius Paul Luntungan; Anggono Anggono Raras Tirto Sakti (Dinasti Publisher, 2025)
This research examines the application of product differentiation and effective digital marketing strategies for revitalizing traditional retail stores, using Kios Maju Berkah as a case study. In an era of increasingly intense competition between traditional retail, modern retail, and e-commerce, traditional stores face significant challenges to survive. This study highlights the importance of unique local products, high-quality customer service, and targeted digital marketing in attracting and retaining customers. Through SWOT and TOWS analysis, this research finds that appropriate product innovation and the implementation of digital marketing strategies can enhance the competitiveness of traditional retail stores. The recommendations from this study include optimizing digital marketing strategies and collaborating with local communities to maintain the relevance and sustainability of traditional retail businesses.